Comparison of blood lactate concentrations obtained during incremental and constant intensity exercise - Foxdal, P.; Sjodin, A.; Sjodin, B. (International Journal of Sports Medicine, 1996)
Differences in blood lactate concentrations obtained during step-wise incremental and constant running exercise at the same intensities were investigated. In addition, the effect of endurance running at a constant intensity obtained by three different incremental modes (OBLA-4, 6 or 8 min) on the blood lactate concentration were studied. Eight firemen and six marathon runners performed: 1) three step-wise incremental running (IR) treadmill tests, each consisting of either 5 x 4, 5 x 6 or 5 x 8 min, and, 2) six 50 min constant intensity running (CR) treadmill tests. Capillary hemolyzed blood was used for lactate determination. The blood lactate during the 5 x 4 min IR-test was 32% (p < 0.001) lower for the firemen and 22% (p < 0.001) lower for the marathon runners compared with the steady state concentration. These differences were diminished in both groups when the 5 x 8 min IR test was used. In the marathon group, constant intensity running at the OBLA intensities obtained by the 5 x 4, 5 x 6 and 5 x 8 min resulted in a lactate accumulation to a mean level of 8.1 mmol.I-1. Also, the marathon runners interrupted the exercise due to maximal perceived exertion after only 19 +/- 3, 26 +/- 4 and 30 +/- 6 min, respectively. In the firemen group, a majority of the subjects were able to complete the 50 min runs, despite a blood lactate accumulation to a mean level of 7.3 mmol.l-1 at the OBLA 5 x 4 and 5 x 6 min intensities. When OBLA 5 x 8 min intensity was performed in this groups, a steady state blood lactate concentration to a mean level of 5.3 mmol.l-1 occurred. It is concluded that step-wise incremental exercise with durations of 4 or 6 min will lead to a high risk of overestimating the maximal lactate steady state exercise intensity and the endurance running capacity.